QUALITY CONTROL OF ELEVATOR AND ESCALATOR MAINTENANCE SERVICES AT PT ABC SURABAYA - Harris, Aulia; Madelan, Sugiyono; Badawi Saluy, Ahmad (Dinasti International Journal of Management Science, 2021)
This study aims to analyze the relationship between service quality, product quality and trust in the decision to use brand image as an intervening medium inservice providers elevator and escalator. This type of research is an explanatory research type using quantitative descriptive research methods. The sample used was 70 respondents. The data was processed using themethod Structural Equation Model-Partial Least Square. The results showed that: (1) service quality and product quality had a positive and significant effect on brand image; (2) service quality, brand image and trust have a positive and significant effect on usage decisions; (3) there is a positive and significant influence between service quality and product quality on the decision to use brand image as a mediating variable.